THE CORRELATION BETWEEN PARENTING STYLE AND STUDENT DEF-T INDEX - Dwi Indah Syaputri; Isnur Hatta; Ika Kusuma Wardani (Universitas Lambung Mangkurat, 2023)
ABSTRACTBackground: Children at primary school age have a special phase in their oral cavity, namely transition phase which is marked by the change of deciduous teeth to permanent teeth. Damage that occurs during this period can affect the condition of the oral cavity and cause various diseases in the future. One of the diseases that often occurs is caries. Based on Riskesdas, the prevalence of caries in Indonesia on 2018 is 57.6% and 59.6% in South Kalimantan. The incidence of caries in children cannot be separated from the parenting provided by parents. Parenting styles are divided into authoritative, authoritarian, and permissive parenting styles. Purpose: To analyze the relationship between parenting style and def-t index of students at SDN Kebun Bunga 4 Banjarmasin. Material and Method: This study used an analytical observational method with a cross-sectional approach. The research sample was 33 students in grades 1-3rd at SDN Kebun Bunga 4 Banjarmasin. Data collection included primary data obtained through direct examination of the students' oral cavity and filling out the PSDQ (Parenting style and Dimensional Questionnaire) to determine parenting styles. The data then processed and analyzed using the SPSS application with Spearman test. Results: The results showed that most parents practice authoritative parenting. The def-t index of students is 6.3 in high category, and there are no parents with authoritarian parenting. Spearman's correlation test showed there was no relationship between parenting style and students' def-t index (p value = 0.371). Conclusion: There is no relationship between parenting styles and students' def-t index.Keywords : Authoritarian, authoritative, parenting style, permissive, student def-t index